P05 Quality of surgical post take ward round documentation by on-call team. (22nd July 2022) - Angamuthu, N; Chowdhury, S; Brothwood, K; Boyle, D
Abstract: Introduction: Documentation of clinical assessment and care plans is integral to patient safety, continuity of care and has medico legal implications. Methods: A retrospective study of the quality of documentation of post take ward rounds (PTWR) by the on-call surgical team was performed. Results: Among the key factors reviewed (18 randomly selected emergency admissions), history of presenting complaints, past history and medical history were recorded in 66%, 72% and 44% of the records respectively. National early warning score (NEWS) was recorded in 66% notes and clinical findings in 88% of patients. The key lab and imaging findings were entered in a subset of patients only (27% and 33% respectively). Based on the initial audit, the PTWR quality could be improved with increased compliance of NEWS score entry, medical history, key lab and imaging results. A standardised ward round template was designed and circulated. This was disseminated to the surgical team by email. Posters were displayed in the surgery office. A presentation was made during teaching session for the junior doctors. The re-audit (34 emergency admissions) showed that the quality had improved based improvement noted in all the key parameters. Documentation of presenting history improved from 66% to 100%. Similarly medical history (44% to 85%), vital signs (66% to 79%), key lab results (27% to 55%), and key imaging (33% to 78%), the management plan was documented in all patients (94% to 100%). Conclusion: In summary, a standardised PTWR entry ensures better quality and compliance; this should be reiterated during junior doctor change over phase. Take-home message: Standardised post take ward round entry ensures quality and better compliance during a busy surgical ward round.